The Effectiveness of Pocket Books on Knowledge about Dental Caries in Grade V and Class VI Students at MI Nurul Hidayah, Gandus Village, Palembang City - Nurhayati, Masayu; Mujiyati, Mujiyati; Hamid, Abu (PT FORMOSA CENDEKIA GLOBAL, 2025)
The purpose of this study is to determine the effectiveness of pocket books in improving dental knowledge among 5th and 6th grade students at MI Nurul Hidayah, Gandus Village, Palembang City. The research method used is a pseudo-experiment with a pre and post-test design. There were 60 students in the study, divided into two groups: the control group and the experimental group. These findings suggest that the experimental group's understanding of dental caries before and after using pocket books differed significantly. Children in grades V and VI have increased their awareness of dental caries by 13% and 10%, respectively, thanks to pocket books. As a result, one of the best learning resources to raise awareness of dental caries in children is the pocket book.